2011
DOI: 10.1002/chem.201100711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Efficiency of the Simultaneous Removal of Metals and Cyanides by Using Ferrate(VI): Crucial Roles of Nanocrystalline Iron(III) Oxyhydroxides and Metal Carbonates

Abstract: The reaction of potassium ferrate(VI), K(2)FeO(4), with weak-acid dissociable cyanides--namely, K(2)[Zn(CN)(4)], K(2)[Cd(CN)(4)], K(2)[Ni(CN)(4)], and K(3)[Cu(CN)(4)]--results in the formation of iron(III) oxyhydroxide nanoparticles that differ in size, crystal structure, and surface area. During cyanide oxidation and the simultaneous reduction of iron(VI), zinc(II), copper(II), and cadmium(II), metallic ions are almost completely removed from solution due to their coprecipitation with the iron(III) oxyhydroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
3

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…[25,26] The encapsulation of arsenic and heavy metals by iron(III) oxide nanoparticles (γ-Fe2O3), generated from Fe(VI), was investigated in detail by in-field Mössbauer spectroscopy. [27][28][29] In the case of arsenic, the results clearly demonstrated that a significant portion of arsenic was embedded in the tetrahedral sites of the γ-Fe2O3 spinel structure.…”
Section: Ferratesmentioning
confidence: 92%
“…[25,26] The encapsulation of arsenic and heavy metals by iron(III) oxide nanoparticles (γ-Fe2O3), generated from Fe(VI), was investigated in detail by in-field Mössbauer spectroscopy. [27][28][29] In the case of arsenic, the results clearly demonstrated that a significant portion of arsenic was embedded in the tetrahedral sites of the γ-Fe2O3 spinel structure.…”
Section: Ferratesmentioning
confidence: 92%
“…Degradation of various pollutants was successfully tested involving pharmaceuticals [18], endocrine disruptors [19], organosulfur compounds [20], pesticides [21], chemical warfare agents [22]. Furthermore, inorganic compounds such as amines [23], cyanides [4] and heavy metals [24]; were investigated with respect to removal by ferrate(VI). In addition to the high efficient removal of pollutants, ferrate(VI) can effectively eliminate water pathogens, bacteria and viruses and acts as disinfection agent [25].…”
Section: Oxidative Action Of Ferrates (Vi)mentioning
confidence: 99%
“…The innovative nanomaterials are beneficial to this purpose because of their high reactivity (especially metallic nanoparticles [1]) and sorption capacity (metal oxide nanoparticles [2]). The iron based materials proved to be promising material due to the availability of iron-bearing precursors and versatility of Fe in its various oxidation states while Fe0/II is a reducing agent [3], FeIV/V/VI is a strong oxidant [4]. Furthermore, the non-toxic iron oxyhydroxides are the final reaction products of Fe-based (nano) materials [5], [6]; these minerals show the similar properties as their naturally occurring analogues [7].…”
Section: Introductionmentioning
confidence: 99%
“…[155,156] Examples include removal of arsenic and metal cyanides by ferrate. [157][158][159][160] When As(III) was oxidized to As(V) by ferrate, Fe(III) oxides/hydroxides formed, which subsequently remove As (V). Importantly, this study demonstrated that the significant portion of arsenic embedded in tetrahedral sites of the γ -Fe 2 O 3 spinel structure.…”
Section: Ferrate(vi) As An Alternate Disinfectantmentioning
confidence: 99%